The prevalence and associated factors of depression, anxiety, and PTSD among Moroccan medical doctors in the COVID-19 pandemic: a national study. Issue 1 (2nd January 2023) - Ouazzani Housni Touhami, Youssef; Maiouak, Moncef; Ouraghene, Amal; Hammani, Zakaria; Abdi, Cheikh Mommed Fadel; Benhammou, Imane; Tahiri, Sophia; Rabhi, Samira; Bennani, Bahia; Bout, Amine; Aarab, Chadya; Boujraf, Said; et al.
ABSTRACT: COVID-19 pandemic is facing healthcare professionals with unprecedented challenges, which might alter their mental health. We targeted assessing depression, generalized anxiety, and post-traumatic stress disorder (PTSD) of Moroccan medical doctors during the COVID-19 pandemic; this would allow identifying the associated factors. A cross-sectional national study was carried out on 1267 exposed and unexposed public health medical doctors to COVID-19 patients. The study was conducted between May 15 and 15 June 2020. An anonymous self-administered questionnaire was completed online voluntarily and randomly. We used the Patient Health Questionnaire (PHQ-9), the Generalized Anxiety Disorder (GAD-7), and the PTSD Checklist for DSM‑5 (PCL-5) to assess depression, generalized anxiety, and PTSD, respectively. The respondents' rate was 63.3%. The mean age was 30.97 ± 6.65 years old, and 59.3% (N = 751) were females with a sex ratio M/F of 0.68. The sample included 43.0% (N = 545) of COVID-19 frontline doctors. Among all participants, 31.5% (N = 400) had depression, 29.2% (N = 370) had generalized anxiety, and 21.7% (N = 276) had PTSD. The average scores of the PHQ-9, the GAD-7, and the PCL-5 were 7.79 (± 5.54), 6.12 (±5.72), and 18.58 (±17.62), respectively. The multivariate logistic regression showed that working in primary and secondary hospitals, moderate and high-stress perceptions, a chronic physical illness, and a family history of psychiatric disorder were independently associated factors of depression, generalized anxiety, and PTSD. The females expressed significantly more anxiety. Doctors living in a family consisting of member with chronic disease showed a significantly higher risk of PTSD. The security sense of contamination risk and low threat perception of COVID-19 were significantly protective factors of depression, anxiety, and PTSD. Moroccan medical doctors are in psychological distress. It is essential to preserve medical doctors' mental well-being health for a better fight against the COVID-19 pandemic through effective and targeted health policies.